How to strengthen a health research system: WHO's review, whose literature and who is providing leadership? - Stephen R. Hanney; Lucy Kanya; Subhash Pokhrel; Teresa H. Jones; Annette Boaz (BMC, 2020)
Abstract Background Health research is important for the achievement of the Sustainable Development Goals. However, there are many challenges facing health research, including securing sufficient funds, building capacity, producing research findings and using both local and global evidence, and avoiding waste. A WHO initiative addressed these challenges by developing a conceptual framework with four functions to guide the development of national health research systems. Despite some progress, more is needed before health research systems can meet their full potential of improving health systems. The WHO Regional Office for Europe commissioned an evidence synthesis of the systems-level literature. This Opinion piece considers its findings before reflecting on the vast additional literature available on the range of specific health research system functions related to the various challenges. Finally, it considers who should lead research system strengthening. Main text The evidence synthesis identifies two main approaches for strengthening national health research systems, namely implementing comprehensive and coherent strategies and participation in partnerships. The literature describing these approaches at the systems level also provides data on ways to strengthen each of the four functions of governance, securing financing, capacity-building, and production and use of research. Countries effectively implementing strategies include England, Ireland and Rwanda, whereas West Africa experienced effective partnerships. Recommended policy approaches for system strengthening are context specific. The vast literature on each function and the ever-growing evidence-base are illustrated by considering papers in just one key journal, Health Research Policy and Systems, and analysing the contribution of two national studies. A review of the functions of the Iranian system identifies over 200 relevant and mostly national records; an analysis of the creation of the English National Institute for Health Research describes the key leadership role played by the health department. Furthermore, WHO is playing leadership roles in helping coordinate partnerships within and across health research systems that have been attempting to tackle the COVID-19 crisis. Conclusions The evidence synthesis provides a firm basis for decision-making by policy-makers and research leaders looking to strengthen national health research systems within their own national context. It identifies five crucial policy approaches - conducting situation analysis, sustaining a comprehensive strategy, engaging stakeholders, evaluating impacts on health systems, and partnership participation. The vast and ever-growing additional literature could provide further perspectives, including on crucial leadership roles for health ministries.